Residual adenoma after cold snare polypectomy for small colorectal adenomas: a prospective clinical study - Maruoka, Daisuke; Arai, Makoto; Akizue, Naoki; Ishikawa, Kentaro; Kasamatsu, Shingo; Taida, Takashi; Ishigami, Hideaki; Okimoto, Kenichiro; Saito, Keiko; Matsumura, Tomoaki; Nakagawa, Tomoo; Katsuno, Tatsuro; Kato, Naoya (Endoscopy, 2018)
Background Endoscopic resection of all colonic adenomas prevents the occurrence of colon cancer and death. The European Society of Gastrointestinal Endoscopy Clinical Guideline recommends resection of all polyps predicted to be adenomas and cold snare polypectomy (CSP) for removal of adenomas ≤ 9 mm on the basis of safety; however, it also states that this recommendation lacks adequate evidence of efficacy. The residual adenoma rate after resection is an important indicator of efficacy, but there have been no reports showing this prospectively. Therefore, we aimed to investigate the residual adenoma rate after CSP of small colonic polyps.Methods Between March 2015 and April 2017, patients who were endoscopically diagnosed with colorectal adenomas < 9 mm underwent CSP, the site being marked with endoscopic clips. Patients with pathologically confirmed adenomas underwent follow-up colonoscopy 3 weeks after CSP and any post-CSP scars were biopsied. The primary endpoint was the presence of pathological residual adenoma 3 weeks after CSP.Results Overall, 126 lesions in 39 patients were removed and 125 (99.2 %) were resected en bloc using CSP. Pathologically, 111 lesions (88.1 %) were confirmed as adenomas (4.2 ± 1.5 mm), with 36 of these (32.4 %) determined to be R0 resections. No complications were observed. All 37 patients with pathologically confirmed adenomas underwent follow-up colonoscopy, and 102 of 111 scars were detected in 33 patients. One pathological residual adenoma (0.98 %, 95 % confidence interval 0.02 % – 5.3 %) was identified.Conclusions CSP appears to be an effective treatment for diminutive and small colorectal adenomas, with a low residual adenoma rate.